2021
DOI: 10.1093/milmed/usaa362
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Energy Drink Consumption and Associated Adverse Effects in Air Force Personnel

Abstract: Introduction Energy drinks are an increasingly utilized beverage and are gaining popularity in recent years. The U.S. Air Force (USAF) represents a unique population where energy drink consumption may be higher than the general population. To better understand the safety and health impact of energy drinks, this large-scale comprehensive survey was conducted to study energy drink consumption patterns and its associated adverse effects. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…According to a report by SAMHSA, the number of emergency department visits due to EDs increased from 10,068 to 20,783 between 2007 and 2011 ( 2 ). In a recent study conducted in Air Force personnel, nearly 1% of energy drink users reported needing to see a physician or going to the emergency department because of adverse effects from energy drinks ( 4 ). The Center for Science in the Public Interest reports 34 deaths linked to energy drink consumption ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to a report by SAMHSA, the number of emergency department visits due to EDs increased from 10,068 to 20,783 between 2007 and 2011 ( 2 ). In a recent study conducted in Air Force personnel, nearly 1% of energy drink users reported needing to see a physician or going to the emergency department because of adverse effects from energy drinks ( 4 ). The Center for Science in the Public Interest reports 34 deaths linked to energy drink consumption ( 5 ).…”
Section: Introductionmentioning
confidence: 99%